2013
DOI: 10.1002/jocb.35
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Mednick's Model on Creativity‐Related Differences in Associative Hierarchies. Evidence for a Common Path to Uncommon Thought

Abstract: Fifty years ago, Mednick [Psychological Review, 69 (1962) 220] proposed an elaborate model that aimed to explain how creative ideas are generated and why creative people are more likely to have creative ideas. The model assumes that creative people have flatter associative hierarchies and as a consequence can more fluently retrieve remote associative elements, which can be combined to form creative ideas. This study aimed at revisiting Mednick’s model and providing an extensive test of its hypotheses. A contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
159
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(185 citation statements)
references
References 50 publications
13
159
0
5
Order By: Relevance
“…One prominent theory supports that high creativity is associated with being able to connect distant concepts, hence promoting the combination of remotely-connected concepts into original ideas (Mednick 1962). Thus, individual differences in creativity may implicate differences in associative processing Gruszka and Necka 2002;Benedek and Neubauer 2013;Kenett et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One prominent theory supports that high creativity is associated with being able to connect distant concepts, hence promoting the combination of remotely-connected concepts into original ideas (Mednick 1962). Thus, individual differences in creativity may implicate differences in associative processing Gruszka and Necka 2002;Benedek and Neubauer 2013;Kenett et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In light of this additional pattern, the active role of tags in mediating the experience of novel ideas appears even more likely. From a learning perspective, this tag-based propagation of ideas is highly desirable, as it seems to broaden and flatten the hierarchy of topic-related associations and thus, supports a more creative encounter with a given topic (e.g., Benedek & Neubauer, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous article, we have especially focused on convergent processes by looking at stabilizing tag vocabulary. In the present article, we draw our attention to the divergent pole of the exploration-exploitation continuum by considering effects of networked search on ideational fluency, a concept from the creative cognition literature (e.g., Benedek & Neubauer, 2013). In the present context, it describes how easily and continuously diverse ideas can be accessed from memory during information-based ideation (Kerne et al, 2008(Kerne et al, , 2014, i.e., when thinking about search topics to be explored in future queries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Network analysis suggests that less creative individuals have a semantic network that is more spread out, more modular, and less connected than more creative individuals (Kenett, Anaki, &Faust, 2014) -though Benedek andNeubauer (2013) did not find that such associative hierarchies differed between less and more creative people. With the exception of Prabhakaran, Green and Gray (2014), who showed that participants given the cue "be creative" produced responses with a higher mean semantic distance, few studies have attempted to systematically manipulate the associative hierarchies, or semantic networks, of participants.…”
Section: Introductionmentioning
confidence: 99%